DESIGN OF FISH SALES INFORMATION SYSTEM IN PT XYZ USING LARAVEL FRAMEWORK - Dimas Aditya Pratama (Penerbitan Universitas Trisakti, 2021)
Development of sales information systems is built to produce an information system that includes various procedures that record, calculate, and make documents in the form of reports for management needs in making decisions, ranging from purchase orders from suppliers, recording inventory of goods, to selling goods to consumers. Information on sales recording activities is still manual so there can be a possibility of entry errors and the presence of branch companies that are late or have not provided a sales report. With the existing problems in this company, then this final project research will create a sales system. Based on these problems, a sales information system was made at PT XYZ. PT XYZ Sales Information System Design uses the waterfall method with php laravel framework in producing a system that will record and update purchase order data, item data, and sales order data and can print reports according to the desired date, month and year.